algebra 116

Rewrite the equation y = 5x – 2 as a function of x.
This problem is already a function of x. y = 5x - 2 as a function of x.

Rewrite the equation –x – 4y = 20 as a function of x.

Graph f(x) = –3x – 2.

Solve the system by graphing.

1. 👍 0
2. 👎 0
3. 👁 101

Similar Questions

1. Calculus urgent

For the intergral of -(x^2)/3 +6 interval [0,3] Rewrite it as a function of n using the right hand endpoint without any summation sign. can anyone help me start this problem out? I noticed somebody else had that post before,

asked by jimmy on April 19, 2007
2. math

rewrite each equation as afunction of x.-3y+4y=11 Where are the equations? rewrite this equation as a function of x.-3y+4y=11 y=x

asked by stacy on February 23, 2007
3. math

For the substitution method, is there a right equation to pick from the set and rewrite it? My problem is 3x-2y=1 2x+4y=1 I chose 2x+4y=2 and came up with x=1-2y which I will later plug into 3x-2y=1. Or do I have to choose

asked by lijm on September 9, 2019
4. Math

How would you rewrite the equation y = 3x+1 as a function of x. Hmmm. It is written now as a function of x. Do you mean like this, where x is a function of y? x= 1/3 y -1 ? Could this be a trick question? I thought It was already

asked by Erin on May 6, 2007
5. Algebra

I have a few questions that I need help with. Solve the radical equation, and check all proposed solutions. 5. x- square root 3x-2=4 I don't understand this problem. Solve and check the equation. 10. (x^2+14x+49)^3/4-20=7 would I

asked by Brit on August 18, 2007
6. Math

The graph of a quadratic function has vertex(3,-4) and passes through the point (4,1). Find the equation of the function in standard form. Rewrite the equation in general form. Could someone explain to me how to do this, just

asked by -Untamed- on December 5, 2011
7. Math

The graph of a quadratic function has vertex(3,-4) and passes through the point (4,1). Find the equation of the function in standard form. Rewrite the equation in general form. Could someone explain to me how to do this, just

asked by -Untamed- on December 5, 2011
8. math

Rewrite the equation 4x – 6y = –30 as a function of x. Subtract 4x from both sides of the equation. Then divide both sides by -6. You should end up with an equation for y, as a function of x.

asked by angel on August 5, 2007
9. Algebra

Rewrite the equation as a function -3x+4y=11 If you want to consider y as a function of x, then y = (1/4)(3x +11) One can also write x as a function of y. x = (1/3)(4y - 11)

asked by Tony on March 16, 2007
10. Algebra

rewrite as an equation as a function of x -3+4=11

asked by Anonymous on September 6, 2007

More Similar Questions